1984
DOI: 10.1557/proc-42-45
|View full text |Cite
|
Sign up to set email alerts
|

Reactions in the Setting of High Strength Cement Pastes

Abstract: Materials of very high flexural strengths (> IOOMPa) can be made by high shear mixing of cement pastes with small amounts of water soluble polymer. Two such systems - high alumina cement/partially hydrolysed polyvinyl acetate and OPC/polyacrylamide - have been examined using a variety of techniques including isothermal calorimetry, infra-red spectroscopy and X-ray diffraction. In both systems the polymer addition appears to become cross-linked by ions released by the cement powder leading to an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…It proves the chemical interaction between the monocalcium aluminate and polymer. According to the main hypothesis of reaction mechanisms, the hydroxyl groups of PVA are crosslinked with the aluminate ions (Al(OH) 4 − ) released during the hydration reaction of the CA phase [22][23][24], which also explains the slight decrease in C\OH contribution compared to the primary PVA. The Ca 2p spectrum of activated CA shows two different kinds of calcium.…”
Section: Resultsmentioning
confidence: 99%
“…It proves the chemical interaction between the monocalcium aluminate and polymer. According to the main hypothesis of reaction mechanisms, the hydroxyl groups of PVA are crosslinked with the aluminate ions (Al(OH) 4 − ) released during the hydration reaction of the CA phase [22][23][24], which also explains the slight decrease in C\OH contribution compared to the primary PVA. The Ca 2p spectrum of activated CA shows two different kinds of calcium.…”
Section: Resultsmentioning
confidence: 99%
“…Further details of the processing (Birchall, 1983), microstructure and reaction mechanisms (Rodgers et al, 1985) have revealed that MDF consists of well packed anhydrous grains bonded together by a complicated hydrate/polymer. Nevertheless the proposition that normal HCP is obeying the Griffith criterion is of great interest; unfortunately the results presented by Birchall et al (1981) showed considerable scatter, thus it is difficult to assign a specific flexural strength-notch length relationship.…”
Section: Biv Strength Of Hcpmentioning
confidence: 99%
“…Especially, very high flexural strengths, 20 or 30 times higher than conventional cement pastes, were easily obtained. The reasons for obtaining such high strengths and superior properties are very low water/cement ratio, crosslinking between polymer and cement, and the unique composition and production process [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%